Dimensions of emerging adulthood, criteria for adulthood, and identity development in Greek studying youth: A person-centered approach - Galanaki, Evangelia; Sideridis, Georgios (Emerging Adulthood, 2019)
Little research has been conducted on emerging adulthood in Greece, although sociodemographic specificities and constraints due to financial crisis are expected to reinforce prolonged transition to adulthood in this Southern European country. Using a person-centered approach, the current study aimed to examine dimensions of emerging adulthood, criteria for adulthood, and identity development among studying youth in association with personal and structural variables (i.e., gender, age, living arrangement, work experience, steady romantic relationship status, and financial adversity). Participants were 814 university students (Mage = 19.9 years). Latent profile analysis yielded five profiles: anxious explorers in-between (29.90%), immature explorers (29.58%), emerging adults (18.30%), adult committers (12.58%), and blocked in transition (9.64%). Significant between-profile differentiation was found regarding all variables except from age and work experience. The results support the existence of emerging adulthood in Greece and indicate diverse paths to adulthood within the rather homogeneous population of studying youth in this country.